Docetaxel plus oxaliplatin with or without fluorouracil or capecitabine in metastatic or locally recurrent gastric cancer: a randomized phase II study - DANE, FAYSAL (ELSEVIER, 2015)
Docetaxel/cisplatin/infusional 5-fluorouracil (5-FU; DCF) is a standard chemotherapy regimen for patients with advanced gastric cancer (GC). This phase II study evaluated docetaxel/oxaliplatin (TE), docetaxel/oxaliplatin/5-FU (TEF), and docetaxel/oxaliplatin/capecitabine (TEX) in patients with advanced GC. Patients with metastatic or locally recurrent gastric adenocarcinoma (including carcinoma of the gastro-oesophageal junction) were randomly assigned (1 : 1 : 1) to TE, TEF, or TEX. Each regimen was tested at two doses before full evaluation at optimized dose levels. The primary end point was progression-free survival (PFS). Overall survival (OS), tumour response, and safety were also assessed. A therapeutic index (median PFS relative to the incidence of febrile neutropenia) was calculated for each regimen and compared with DCF (historical data). Overall, 248 patients were randomly assigned to receive optimized dose treatment. Median PFS was longer with TEF (7.66 [95% confidence interval (CI): 6.97-9.40] months) versus TE (4.50 [3.68-5.32] months) and TEX (5.55 [4.30-6.37] months). Median OS was 14.59 (95% CI: 11.70-21.78) months for TEF versus 8.97 (7.79-10.87) months for TE and 11.30 (8.08-14.03) months for TEX. The rate of tumour response (complete or partial) was 46.6% (95% CI 35.9-57.5) for TEF versus 23.1% (14.3-34.0) for TE and 25.6% (16.6-36.4) for TEX. The frequency and type of adverse events (AEs) were similar across the three arms. Common grade 3/4 AEs were fatigue (21%), sensory neuropathy (14%), and diarrhoea (13%). Febrile neutropenia was reported in 2% (TEF), 14% (TE), and 9% (TEX) of patients. The therapeutic index was improved with TEF versus TEX, TE, or DCF. These results suggest that TEF is worthy of evaluation as an arm in a phase III trial or as a backbone regimen for new targeted agents in advanced GC.
Keywords: antineoplastic agents; combined; platinum compounds; stomach neoplasms; taxoids; GASTROESOPHAGEAL JUNCTION; 1ST-LINE THERAPY; CISPLATIN; TRIAL; ADENOCARCINOMA; COMBINATION; EPIRUBICIN; CHEMOTHERAPY; DOXORUBICIN; MITOMYCIN